FESTIVAL LOMBA WARNA-WARNI TINGKAT TK DAN PAUD SEKAB. AGAM DAN KOTA BUKITTINGGI UNTUK MENARIK MINAT PENGUNJUNG PADA OBJEK WISATA BONTO ROYO - Indriani, Jennisa Dwina; Kuliman, Kuliman; Avis, Mairinal; Nugroho, Rizky Adhitya; Nazif, Muhammad; Putri, Anne; Mustaqimah, Sri Asyrafil; Rahmawaty, Dian (Fakultas Teknik, Universitas Bangka Belitung, 2024)
The Banto Royo tourist attraction is one of the tourist destinations located in Nagari Koto Tangah, Tilatang Kamang District, Agam Regency. At the beginning of its appearance, the Banto Royo tourist attraction seemed to be the main destination that people had to visit. However, after the Covid-19 pandemic that hit the world some time ago, it also had a significant impact on the Banto Royo tourist attraction. Therefore, Community Service is carried out in the Banto Royo tourist attraction area in order to attract visitors' interest in traveling to this tourist attraction. The method for implementing this Community Service activity is to carry out an event that can attract the interest of visitors, namely by holding a Colorful Festival at Kindergarten and Preschool Levels throughout Agam district and Bukittinggi city. This activity aims to reintroduce the Banto Royo tourist attraction to the community and attract tourist interest. With an increase in tourist visits, it is hoped that it will increase the income of this tourist attraction and the income of the surrounding community.